ANALISIS HIGIENE DAN SANITASI KANTIN DI PT X TAHUN 2022 - Sartika Aliffia, (2023)
Health problems can be caused by food, so hygiene and sanitation must be implemented in the canteen. The purpose of this study was to analyze canteen hygiene sanitation at PT X in 2022. This was qualitative research with a descriptive study design. The data collection methods used were interviews and observations. The analysis techniques were reduction, presentation, and data verification. Informants who consisted of GA managers, QA staff, and food handlers were selected by a purposive sampling technique. The results showed that the building variable met 88% of requirements in canteen A, 88% in canteen B, and 52% in canteen C. The Sanitation Facilities variable met 87.5% of requirements in canteen A, 100% in canteen B, and 87.5% in canteen C. Equipment variables met 100% of requirements in canteen A, 82.6% in canteen B, 73.9% in canteen C. Employee variables met 100% of requirements in all canteens. The food variable met 100% of requirements in all canteens. As conclusions, several aspects of the building, sanitation facilities, and equipment variables have been carried out in accordance with the regulations and all aspects of the employee and food variables have been carried out according to the regulations.